2022
DOI: 10.1021/acsapm.2c01527
|View full text |Cite
|
Sign up to set email alerts
|

Modified CARDO-Based Copolyimides with Improved Sour Mixed-Gas Permeation Properties

Abstract: Chemical modification is an interesting tool to introduce functional groups into polymers’ backbones to tailor their properties in a desired fashion. Polymers used in membrane-based gas separation applications need to possess high gas permeability and selectivity during mixed-gas separation under harsh operational conditions of pressure and temperature. Herein, we report the modification of three copolyimides containing the moiety 9,9-bis­(4-aminophenyl)­fluorine (CARDO) through Friedel–Crafts alkylation to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…11,27−31 The CARDO(OH) monomer is a derivative of the CARDO monomer [9,9-bis(4-aminophenyl)fluorene], which was studied thoroughly by our group. 10,11,27,28,32 Interestingly, the chemical structure of CARDO(OH) includes two hydroxyl groups located at the 2 and 7 positions of its fluorene moiety. These hydroxyl groups can act as (1) bulky groups within the polymer backbone to enhance the diffusion of gas molecules [i.e., V W of CARDO = 321.6 Å 3 and V W of CARDO(OH) = 338.5 Å 3 ], (2) polar groups to increase the gas-polymer interaction (i.e., higher solubility), and (3) sites for thermal cross-linking.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…11,27−31 The CARDO(OH) monomer is a derivative of the CARDO monomer [9,9-bis(4-aminophenyl)fluorene], which was studied thoroughly by our group. 10,11,27,28,32 Interestingly, the chemical structure of CARDO(OH) includes two hydroxyl groups located at the 2 and 7 positions of its fluorene moiety. These hydroxyl groups can act as (1) bulky groups within the polymer backbone to enhance the diffusion of gas molecules [i.e., V W of CARDO = 321.6 Å 3 and V W of CARDO(OH) = 338.5 Å 3 ], (2) polar groups to increase the gas-polymer interaction (i.e., higher solubility), and (3) sites for thermal cross-linking.…”
Section: T H Imentioning
confidence: 99%
“…Therefore, the permeation through the membrane depends strongly on the solubility and diffusivity of the gas molecules, and the overall membrane performance relies on the difference between the solubility and diffusivity coefficients of those molecules. Hence, introducing new functional groups into the polymer’s backbone can (1) enhance the excess free volume within the membrane structure by altering the interchain packing (i.e., faster diffusion) or (2) increase the polymer-gas interaction to improve the gas molecules solubility. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published data on membranes for CO 2 removal are done under close‐to ideal conditions, using pure‐gas permeation properties as performance indicators 16 . Several studies have demonstrated that the performance of membrane‐based CO 2 removal from mixed‐gas streams containing CH 4 , heavy hydrocarbons and inert gases deviates significantly from pure‐gas properties, due to a combination of competitive sorption, membrane plasticization, concentration polarization and convective mass transfer 17–23 . Additionally, most of the membranes reported in literature are characterized and tested using simple dense‐film geometry (i.e., planar geometry).…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies have demonstrated that the performance of membrane-based CO 2 removal from mixed-gas streams containing CH 4 , heavy hydrocarbons and inert gases deviates significantly from pure-gas properties, due to a combination of competitive sorption, membrane plasticization, concentration polarization and convective mass transfer. [17][18][19][20][21][22][23] Additionally, most of the membranes reported in literature are characterized and tested using simple dense-film geometry (i.e., planar geometry). For large-scale industrial membrane-based application of gas separation, in particular, asymmetric or composite hollow fiber (i.e., tubular geometry) is often preferred, owing to its high packing density, resistance to high transmembrane pressures, and the ability to create ultra-thin selective layers.…”
Section: Introductionmentioning
confidence: 99%